Chromatin-Associated Protein Sugp2 Involved in mRNA Alternative Splicing During Mouse Spermatogenesis - Zhan, Junfeng; Li, Jianbo; Wu, Yuerong; Wu, Panfeng; Yu, Ziqi; Cui, Peng; Zhou, Mofan; Xu, Yumin; Jin, Tingyu; Du, Ziye; Luo, Mengcheng; Liu, Cong (Frontiers in Veterinary Science, 2021)
Mammalian spermatogenesis is a highly ordered process that is determined by chromatin-associated moderators which still remain poorly understood. Through a multi-control group proteomics strategy, we confirmed that Sugp2 was a chromatin-associated candidate protein, and its signal arose along spermatogenesis. The expression results showed that Sugp2, which is mainly expressed in the testis, had two transcripts, encoding one protein. During spermatogenesis, Sugp2 was enriched in the nucleus of male germ cells. With the depletion of Sugp2 by CRISPER-Cas9 technology, we found that Sugp2 controlled a network of genes on metal ion and ATP binding, suggesting that alternative splicing regulation by Sugp2 is involved in cellular ion and energy metabolism during spermatogenesis, while it had a little effect on meiotic progression and male fertility. Collectively, these data demonstrated that, as a chromatin-associated protein, Sugp2 mediated the alternative splicing regulatory network during spermatogenesis.